C9orf72 expansion presenting as an eating disorder. (March 2016) - Sanders, Peter; Ewing, Isobel; Ahmad, Kate
Highlights: The predominant frontotemporal dementia (FTD) phenotype associated with the C9orf72 mutation is that of behavioural variant frontotemporal dementia (bvFTD). C9orf72 can present with anorexia rather than the hyperphagia usually seen with bvFTD. C9orf72 mutation carriers may present with heterogeneous clinical syndromes. Abstract: This report describes a 64-year-old woman with a strong family history of motor neuron disease, whose diagnosis of behavioural variant frontotemporal dementia was delayed due to her initial presentation with atypical manifestations, including restriction of oral intake resulting in low weight, disordered eating and anxiety. Upon investigation, she was found to be a carrier of the C9orf72 hexanucleotide repeat expansion. Our case supports previous publications asserting that C9orf72 mutation carriers manifest with diverse clinical syndromes, and expands the phenotype to include anorexia and food refusal as potential features of the condition.